A new species of Elaphoglossum sect. Lepidoglossa (Dryopteridaceae) from Bolivia - Kessler, Michael (Phytotaxa, 2013)
Elaphoglossum dannoritzeri from Bolivia is described as a geographical vicariant distinct from E. mathewsii (Costa Rica to Peru, Chile) based on its medium brown, entire to subdenticulate rhizome scales (versus dark brown, denticulate), narrower and relatively longer petiole scales with few or no sclerotic cells and no or only slightly developed pale margins, longer creeping rhizomes with more widely spaced petioles, less dense adaxial blade scale cover, and smaller spores.